2015
DOI: 10.1074/jbc.m114.616888
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Inhibits Osteopontin-dependent Transforming Growth Factor-β1 Expression in Human Mesenchymal Stem Cells

Abstract: Background: Alcohol (EtOH) exposure has detrimental effects on fracture healing. Results: EtOH inhibits TGF-␤1 protein expression via interference with the transcription factor myeloid zinc finger 1. Conclusion: EtOH-induced deficient fracture healing may be related to reduced TGF-␤1. Significance: Further understanding of the mechanisms responsible for the effects of EtOH are crucial for the development of interventions aimed at averting morbidities related to EtOH consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 33 publications
(37 reference statements)
0
26
0
1
Order By: Relevance
“…Animal studies also indicated decreased osteogenesis and bone volume after long-term alcohol consumption [9, 10]. Human bone mesenchymal stem cells (hBMSCs) are regarded as the main source of self-renewal and regeneration of bone tissue [11-13], whereas recent studies demonstrated that ethanol treatment could impair the osteogenic differentiation of hBMSCs [2, 14]. Meanwhile, suppressed osteogenic activity has been detected in ONFH patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies also indicated decreased osteogenesis and bone volume after long-term alcohol consumption [9, 10]. Human bone mesenchymal stem cells (hBMSCs) are regarded as the main source of self-renewal and regeneration of bone tissue [11-13], whereas recent studies demonstrated that ethanol treatment could impair the osteogenic differentiation of hBMSCs [2, 14]. Meanwhile, suppressed osteogenic activity has been detected in ONFH patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the L/BD regional cluster analysis identified 9 DMRs, 4 of which mapped to genes with known links to alcohol use ( PDE10A, CCBE1, FZD5, MZF1 ) (Driver et al, 2015; Edenberg et al, 2010; Logrip, 2015; Wang et al, 2016). The other 5 DMRs map to 4 genes of relevance to synaptic signaling ( PKD2L2, FXDY5, TRAPPC9, MACROD1 ) (Fiederling et al, 2011; Georgolios et al, 2012; Hu et al, 2005; Spanagel et al, 2014; Wu et al, 2011) although this is the first report to specifically link them to sustained levels of voluntary alcohol drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that moderate alcohol consumption has a protective anti-inflammatory role by inhibiting NF-κβ activation (Mandrekar et al, 2007), however our studies hint that NF-κβ mediated mechanisms may also play a role in regulating alcohol consumption. A downstream target of the AC/cAMP/PKA pathway recently identified as a target of alcohol is the transcription factor of the Kruppel family of zinc finger proteins encoded by MZF1 (Driver et al, 2015; Luo et al, 2009). While the role of MZF1 in the brain is currently unknown, it was found that ethanol interfered with the phosphorylation and transcriptional activation of MZF1 in mesenchymal stem cells, ultimately impairing bone healing (Driver et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCECs were treated with human osteopontin recombinant protein (rhOPN; R&D Systems) at a final concentration of 180 ng mL −1 ) or 4E1RC at 1 h after treatment with the OPN neutralizing antibody. After pretreatment, HCECs were treated with A. fumigatus conidia at an MOI of 1 for 0 and 16 h in 12‐well plates for qRT‐PCR and 0 and 16 h in 6‐well plates for western blotting.…”
Section: Methodsmentioning
confidence: 99%